Tailored Approach in Adrenal Surgery: Retroperitoneoscopic Partial Adrenalectomy - Alesina, Pier Francesco; Knyazeva, Polina; Hinrichs, Jakob; Walz, Martin K. (Frontiers in Endocrinology, 2022)
The interest on partial adrenalectomy has steadily increased over the past twenty years. Adrenal pathologies are mostly benign, making an organ-preserving procedure attractive for many patients. The introduction of minimally invasive techniques played probably an important role in this process because they transformed a complex surgical procedure, related to the difficult access to the retroperitoneal space, into a simple operation improving the accessibility to this organ. In this review we summarize the role of partial retroperitoneoscopic adrenalectomy over the years and the current indications and technique.